P297 Evaluation of the clinical course of Adolescent inflammatory bowel disease patients at Nottingham University Hospital. (16th January 2018) - Osei-Bordom, D -c; Thi, A A; Williams, E; Yusoff, N; Ahmad, N; Horne, T; Abbasi, F; Mildrid, Y; Devadason, D; Simon, E; Card, T; Moran, G
Abstract: Background: The incidence of inflammatory bowel disease (IBD) is increasing with 10- 25% were diagnosed in the paediatric and adolescent population. For the young people and adolescents with IBD, they are more susceptible to more severe and extensive forms of the disease and require consistent and clear progression through their treatment pathway, from paediatric to adult care. Methods: Aims 1. To identify the IBD young adult at Nottingham University Hospital (NUH) NHS Trust between the period January 2000- May 2016. 2. to review the previous medical and surgical treatments of young IBD patients at the time of presentation to adult care Method All young IBD patients were identified retrospectively from the IBD transition clinic between 2009 – 2016, the adult gastroenterology clinic with the age group 16 to 34 years during the period June 2014 to May 2016 and all inpatient IBD patient aditted between January 2000- May 2016 by using ICD code. We elicited the participants' backgrounds, disease pathway, including: age at diagnosis, first liaison with the tertiary centre, location of as Crohn's disease (CD) and ulcerative colitis (UC) or Indeterminate colitis (IBDU), whether any IBD-related surgeries has taken place, attendance to a transition clinic and current medications. Results: We identified 373 paediatric onset IBD patients, with 242 (65%) having CD, 110 (30 %) UC and 21 (5%) IBDU during the study period. 23/373 (6 %) were having their diagnosis changed prior to transition. The mean age of diagnosis was 13.8 years (range 6- 18), 60% were male and 247 (66%) patients were diagnosed at NUH. 300 (80%) patients were diagnosed at a paediatric gastroenterology clinic and 184/300 (61%) were attended the transition clinic at NUH. Seventy-three (20%) adolescents were diagnosed at the adult gastroenterology clinic. Total 306 (82 %) patients were still under the care of NUH. 127/373 (34%) had IBD-related operation and 102/127 (80%) were CD. 93/373 patients (24%) were having combination therapy with anti-TNF and thiopurine. 179/373 (48%) were on Immunomodulators and 99/373 (27%) were on anti TNF at the time of study. Conclusions: One third of patient underwent surgery early in the disease course prior to transition and the majority were CD. Nearly half of these patients were on immunomodulators and one quarter were on anti-TNF treatment at the time of study. Paediatric onset IBD patients in this cohort have severe course and significant burden on the paediatric patients and required successful transition to adult care.